A New Non-linear H-infinity Feedback Control Approach for Three-phase Voltage Source Converters. Issue 3 (7th February 2016) - Rigatos, Gerasimos; Siano, Pierluigi; Cecati, Carlo
Abstract : Abstract — This research work introduces a new method for feedback control of power electronics with non-linear dynamics, using as an application example the problem of three-phase voltage source converters. The control method consists of a repetitive solution of an H -infinity control problem for the voltage source converter, based on a locally linearized model of the converter, and takes place at each iteration of the control algorithm. The converter's model is locally linearized around its current operating point through the computation of the associated Jacobian matrices. Using the linearized model of the converter, an H -infinity feedback control law is computed. The known robustness features of H -infinity control enable compensation for the errors of the approximate linearization, as well as elimination of the effects of external perturbations. The efficiency of the proposed control scheme is shown analytically and is confirmed through simulation experiments. The method can be also applied to other power electronics models.